(untitled) (Tzintzun, Revista de Estudios Históricos, 2024)
The promulgation of the bull Ineffabilis Deus in 1854 and with it the elevation of the mystery of the Immaculate Conception to dogma, constituted the prelude to the dogmatic proclamation of papal infallibility in 1870. The objective of this text is to analyze in a comparative way the political-religious scenarios that ruled both in Mexico and Spain and their transcendence for the Pase Regio or the Pase Nacional of this important bull that, theologically, put an end to the old spiritual discussions about the pure nature of Mary, but politically, it was the combative materialization of the papacy to recover its questioned temporal power.